Prevalence of multi-antibiotics resistant (MAR) Vibrio parahaemolyticus in shrimp farms in Sarawak, Malaysia - Elexson, Nillian; Eddy, M. B.; Wong, J.C.J; Lesen, D.; Ransangan, J.; Thung, T.Y. (Rynnye Lyan Resources, 2023)
The shrimp farming industry is constantly under threat due to outbreaks of infectious diseases and environmental problems. Vibrio parahaemolyticus is an important foodborne pathogen causing significant economic losses within the shrimp aquaculture industry worldwide. This research aimed to determine the prevalence of V. parahaemolyticus from different shrimp farms from the stocking to harvesting period and assess the antibiotic susceptibility of V. parahaemolyticus using the antimicrobial susceptibility test (AST). In this study, a total of 288 samples comprising twenty-four from each sample consisting of shrimp, water, effluent, and sediment samples were collected aseptically from three (n = 3) shrimp farms located at Telaga Air Farm 1 (Pond 6), Telaga Air Farm 2 (Pond 9) and Santubong Farm (Pond 7), Kuching, Sarawak. A molecular approach by polymerase chain reaction was used to confirm the presence of regulator gene, toxR, V. parahaemolyticus. A total of 14 antibiotics, including spectinomycin (SH100), imipenem (IPM10), amoxycillin/clavulanic acid (AMC30), enrofloxacin (ENR5), bacitracin (B10), meropenem (MEM10), cephalothin (KF30), penicillin G (P10), tetracycline (TE30), kanamycin (K30), streptomycin(S25), rifampicin (RD2), erythromycin (E15), and nalidixic acid (NA30) were used. The results obtained showed that 51/288 (17.71%) of the collected samples with regulator gene, toxR V. parahaemolyticus. As a whole, this includes 31.25% (30/288) from sediment samples, 4.17% (4/288) from shrimp samples, 15.63% (15/288) from water samples, and 2.08% (2/288) from effluent water samples. A total of 54.9% (28/51) of V. parahaemolyticus acquired multiple antibiotic resistance (MAR). The resistance of antibiotics was profiled, and the multiple antibiotic resistance (MAR) indexes and classified into ten patterns. The MAR index of V. parahaemolyticus isolates ranged from 0.11 to 0.36. Vibrio parahaemolyticus isolates showed 31.38% with a MAR index > 0.2, indicating that these isolates might be originated from high-risk sources. The data obtained from this study is helpful to monitor the presence of V. parahaemolyticus in the aquaculture farm management system to mitigate the hazard potentially arising from the environmental factor that causes shrimp diseases and shrimp infection.